Ukrainian National Dumas: National Perceptions in the Process of Intercultural Communication - Maryna Nabok (Психолінгвістика, 2018)
The article presents the results of empirical research on ethnopsychological groups of people living in different regions of Ukraine in the context of intercultural ideological systems. In particular, residents of Ukraine and foreign students from Africa and Middle East, which study at Sumy State University, were invited to share their impressions from the listened dumas, performed by Canadian bandurist Victor Mishalow during his concert tour in Ukraine. They also watched and listened to video recordings of such folk dumas as «Cossack Golota», «Marusya Boguslavka» performed by kobzar Mykola Budnyk and bandura player Fedir Zharko. Students analyzed the characters’ images, expressed their understanding and attitude to characters’ actions and compared them with the national heroes of their own countries.